Teaching Two Critical Locomotor Skills to Children who Are Blind or Have Low Vision. (March 2015) - Samalot-Rivera, Amaury; Lieberman, Lauren J.; Haibach, Pamela
Alexandria has retinopathy of prematurity. While attending elementary school, she received the services of a teacher of visually impaired students, an adapted physical education teacher, and an orientation and mobility instructor. Her instructors praised her running and never provided any constructive feedback on the movement patterns of her running, so Alexandria assumed that she was running with proper form. It was not until Alexandria advanced to middle school that a physical educator informed her that she had a shuffling gait and needed to swing her arms while running. Through tactile modeling and physical guidance, Alexandria's gait improved dramatically; however, she was embarrassed that her form was not corrected at a younger age.